Anti-money Laundering Awareness and Acceptance among the Banking Customers of Nepal (Quest Journal of Management and Social Sciences, 2020)
Background: Money laundering is a process of converting illegal money into legal money. This process is considered a challenging phenomenon for the financial system. To stop this exploitation of the financial system, anti-money laundering (AML) regimes are formulated. However, the general public acceptance is crucial to make the framework viable. Public awareness of Anti-money Laundering (AML related factors helps people enforce the AML regimes properly.Objective: The paper aims to examine the relationship between awareness of AMLrelated factorsand acceptance ofAMLregimes. Along with that, the study accessesthe level of awareness and level of acceptance among bank clients about AML factors and AML regimes respectively.Methods: Based on descriptive and inferential research designs, the study made use of primary data collected through a structured questionnaire surveyed on 168 bank customers who are of 18 years and above, using a convenience sampling technique. Descriptive analysis is used to access the level of awareness and acceptance, whereas the relationship between awareness and acceptance is examined through correlation and regression analysis.Results: Bank customers are moderately aware of money laundering (ML) andterrorism financing (TF), and anti-money laundering (AML)along with Know Your Customer (KYC).However, they are somewhat and slightly aware of AML investigation agency and AML legislation respectively. Similarly, they have a slightacceptance attitude towards all AML regimes. There is a significantlypositive relationship between awareness of AML related factors and acceptance for AML regimes.Conclusions: Bank customers of Nepal have a comparatively higher awareness of ML, TF, AML and KYC than that of AML legislation and AML investigating agency. However, they have a similar acceptance attitude towards all three AML regimes. Acceptance for AML regimes can be increased by enhancing the awareness of AML related factors among the bank customers. The study, therefore, recommends the concerned authority like FIU-Nepal and NRB to undertake public awareness campaigns in related areas.Implication: Study findings can be useful to policymakers and concerned authorities to formulate positive national policies sensitive to AML.